How does sharia compliance affect the fraud of the Islamic bank? - Rizki Dwi Anggraini; Rossje V. Suryaputri (Jurnal Akuntansi Aktual, 2023)
This study aimed to examine the Effect of Shariah Compliance on Fraud in Islamic Banks. The independent variable of this study is shariah compliance proxied by Islamic Income Ratio (IsIR), Zakat Performance Ratio (ZPR), and Islamic Investment Ratio (IsIVR). In comparison, the control variables used Islamic Corporate Governance (ICG) and Profit Sharing Ratio (PSR). The dependent variable used is Fraud in Islamic Banks. The sample in this study used a purposive sampling technique, namely 7 Islamic Banks with 42 observations. The observation period was from 2016-2021 and the data analysis method used the data regression panel which was processed using E-views 9 software. Based on the test results, it was shown that the Zakat Performance Ratio (ZPR) effect Fraud Islamic Banks, while Islamic Income Ratio (IsIR) and Islamic Investment Ratio (IsIVR) do not affect Fraud Islamic Banks.AbstrakPenelitian ini bertujuan untuk menguji Pengaruh Sharia Compliance terhadap Fraud pada Bank Syariah. Variabel independen penelitian ini adalah Sharia Compliance yang diproksikan dengan Islamic Income Ratio (IsIR), Zakat Performance Ratio (ZPR) dan Islamic Investment Ratio (IsIVR). Sedangkan variabel kontrol menggunakan Islamic Corporate Governance (ICG) dan Profit Sharing Ratio (PSR). Variabel dependen yang digunakan adalah Fraud pada Bank Syariah. Sampel dalam penelitian ini menggunakan teknik purposive sampling yaitu 7 Bank Syariah dengan jumlah observasi sebanyak 42 data. Periode penelitian ini dari tahun 2016-2021 dan metode analisis data menggunakan panel regresi data yang diolah menggunakan software E-views 9. Berdasar dari hasil pengujian diketahui bahwa Zakat Performance Ratio (ZPR) berpengaruh terhadap Fraud Bank Syariah, sedangkan Islamic Income Ratio (IsIR) dan Islamic Investment Ratio (IsIVR) tidak berpengaruh terhadap Fraud Bank Syariah.